Research on contradictions and priorities in integrated planning of the coastal space in Hai Hau - Nghia Hung districts, Nam Dinh province - Lam, Hoang Quoc; Thinh, Nguyen An (Vietnam Journal of Marine Science and Technology, 2020)
Hai Hau - Nghia Hung are two coastal districts in the Southeast of Nam Dinh province with total area of 35,652.29 km2. Located in the middle between the Southern provinces of the Red river delta and the North Central provinces, Hai Hau and Nghia Hung are about 100 km from Hanoi along National Route 1A and 80 km from Hai Phong, in an area directly affected by the Hanoi - Hai Phong - Quang Ninh growth triangle. The two districts have an approximately 47 km coastline accounting for over 65% of the coastline of the province. Along the coastline there are four rivers: Red river, So river, Ninh Co river and Day river emptying into the sea through the estuaries: Ba Lat, Ha Lan, Ninh Co and Day, which facilitate the development in industry, agriculture, sea ports, trade, tourism... This is also a region with high-speed economic development and a series of plannings. Thus, a number of conflicts in exploiting and using natural resources and environmental protection have been raised, leading to destroyed sceneries, lost ecological balance, and becoming an anxious problem. This paper presents experimental results in defining the conflicts and priorities between sectors and economic fields in integrated coastal space planning of Hai Hau - Nghia Hung districts to select the economic sectors that have the most potential and advantages. Therefore, it will be appropriate in space usage in exploiting and using natural resources and environmental protection, which will provide the basis for the development of a sustainable marine economy.